Duranta erecta, Golden Dewdrop - Michael G. Andreu; Melissa H. Friedman; Mary McKenzie; Heather V. Quintana; Robert J. Northrop (EDIS, 2010)
FOR 265, a 2-page fact sheet by Michael G. Andreu, Melissa H. Friedman, Mary McKenzie, Heather V. Quintana, and Robert J. Northrop, describes this small evergreen tree found in the sun belt of the United States, including Florida, Louisiana, Texas, Arizona, California, and Hawaii – scientific and common names, description, allergen, and applications. Includes references. Published by the UF School of Forest Resources and Conservation, June 2010.